The Sphere of Cognitive Narratology - Peternai Andrić, Kristina; Kluiser, Viktoria (Anafora, 2023)
The paper thematizes cognitive narratology as a direction developed within postclassical and new narratologies by observing it in a series of related concepts such as cognitive poetics, cognitive linguistics, cognitivism, and evolutionary literary theory. It delineates its scope and reach within cognitive science, and discusses concepts such as schemata, frames, narrativity, parables, and others, which can influence the development and transformation within cognitive narratology.